Analisis Bibliometrik Perkembangan Aplikasi DNA Barcode pada Tanaman Buah di Indonesia - Sumarlina, Sumarlina; Napitupulu, Tia Sofiani (Jurnal Kridatama Sains dan Teknologi, 2025)
Biodiversity studies using molecular approaches have been widely conducted, one of which is with the application of DNA barcodes. As a megabiodiversity country, Indonesia has many plant commodities that continue to be developed, including fruit plants. This study aims to analyze the development of DNA barcode applications in fruit plants in Indonesia using a literature study method with a bibliometric and substantial analysis approach. The study was conducted through three main stages, namely searching for published literature in the period 2000 - 2025 with the Publish or Perish application, bibliometric analysis with VOSviewer, and substantial analysis. The results of the study show that research related to DNA barcode applications in fruit plants in Indonesia has increased in number and diversity of topics. There are 4 keyword clusters formed in the visualization results, which show a shift in keywords from a focus on identifying morphological characters to molecular-based identification through DNA analysis. This is related to the development of technology and molecular analysis methods which are also developing rapidly. The DNA barcode loci studied can come from nuclear DNA or chloroplast DNA in various plant families, with the most studied taxa levels being at the genus and species levels. In addition, in silico approaches that utilize secondary DNA barcode data have also been widely studied in Indonesia in recent years